Janina Katz in memoriam - Apelt, Helene (Rambam. Tidsskrift for jødisk kultur og forskning, 2014)
Janina Katz in Memoriam The poet and writer Janina Katz was tired of being labelled an “exile author”. Born and raised in Poland and arriving in Denmark at the age of 30, she wished to be judged by the same standards as other authors. But it is hard to ignore the fact that her fate was so different from most of her Danish colleagues. Her experiences reflect the 20th century’s great tragedies of divided families, genocide and ruptured landscapes. Living a life with traumas in the shadow of anti-Semitism and communism, her personal story reflects a remarkable Jewish fate in the 20th century with themes such as exile, displacement and survival against all odds. These themes are also evident in her literary work, where she wrestles with immigrant life, multilingualism and an almost schizophrenic split between Judaism and Catholicism. Helene Apelt writes a portrait in memoriam of this charismatic woman, who with her sharp, penetrating voice could tell of her experience of deprivation and passion in an edgy Danish language with a sense of gallows humour. A writer and a poet who has carved her way through the literary landscape and created her own space on the literary scene, Janina Katz died in October 2013, 74 years old.